2021
DOI: 10.1021/acs.jpca.0c10313
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Solvent Environment on the Ultrafast Relaxation Pathways of a Sunscreen Molecule Diethylamino Hydroxybenzoyl Hexyl Benzoate

Abstract: The excited-state dynamics of photoexcited diethylamino hydroxybenzoyl hexyl benzoate (DHHB), a UVA absorber widely used in sunscreen formulations, are studied with transient electronic and vibrational absorption spectroscopy methods in four different solvents. In the polar solvents methanol, dimethyl sulfoxide (DMSO) and acetonitrile, strong stimulated emission (SE) is observed at early time delays after photoexcitation at a near-UV wavelength of ex = 360 nm, and decays with time constants of 420 fs in metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…In view of the attention that nowadays is given to protection against solar radiation and the potential of photothermal materials, it is not surprising that over the years increasingly more studies have been reported that focus on these aspects. The development of spectroscopic techniques that enable such studies over a wide range of wavelengths, encompassing time scales ranging from femtoseconds to days and longer, and under a large variety of environmental conditions [18][19][20][21][22][23][24][25][26][27] in combination with advanced quantum chemical calculations [28][29][30][31][32][33] has from this point of view contributed significantly to the body of knowledge that is currently available.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the attention that nowadays is given to protection against solar radiation and the potential of photothermal materials, it is not surprising that over the years increasingly more studies have been reported that focus on these aspects. The development of spectroscopic techniques that enable such studies over a wide range of wavelengths, encompassing time scales ranging from femtoseconds to days and longer, and under a large variety of environmental conditions [18][19][20][21][22][23][24][25][26][27] in combination with advanced quantum chemical calculations [28][29][30][31][32][33] has from this point of view contributed significantly to the body of knowledge that is currently available.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Transient electronic absorption spectroscopy (herein abbreviated as TEAS), is an ultrafast pump-probe technique that has been utilised previously to explore the photoprotection mechanisms of many individual UV filters in solution, including avobenzone; additional examples include benzophenone-3, ethylhexyl methoxycinnamate, homosalate, ethylhexyl salicylate, octocrylene and diethylamino hydroxybenzoyl hexyl benzoate. [23][24][25][26][27][28] An ideal sunscreen filter should be able to dissipate excited state energy safely (ideally non-radiatively) and rapidly (within femtoseconds, 1 fs = 10 À15 s, to picoseconds, 1 ps = 10 À12 s). This reduces the likelihood of harmful side reactions such as forming triplet states, or fragmentation of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Computational methods such as density functional theory (DFT), including time-dependent DFT (TD-DFT), can also be used to guide the assessment of a molecule's suitability for sunscreen use. 28,34,35 As an example, Wang et al include both experimental (including ultrafast) data and computational methods in their study of UV-induced photochemical reactions in diketo avobenzone derivatives. 36 However, TEAS studies have not been widely used in conjunction with industry-standard efficacy tests that sunscreen formulations are subject to, such as sun protection factor (SPF) and UVA protection factor (UVA-PF) determination.…”
Section: Introductionmentioning
confidence: 99%
“…This work complements the gas-phase work described above since it provides insight into how bulk solvation impacts on the intrinsic sunscreen photophysics. A study of diethylamino hydroxybenzoyl in four different solvents (i.e., methanol, dimethyl sulfoxide, acetonitrile, and cyclohexane) by Orr-Ewing and co-workers provides a recent example ( Kao et al, 2021 ). Work in this area has been previously reviewed by Stavros and co-workers ( Rodrigues and Stavros, 2018 ; Holt et al, 2020 ) so we refer the reader to the reviews for further information.…”
Section: How Does Changing the Solvent Affect Sunscreen Performance?mentioning
confidence: 99%